The Impact of Tap Connection on Water Use : The Case of Household Water Consumption in Dakar, Senegal - Briand, Anne (2012)
Predicting residential water demand for non-connected households that obtain connections is a crucial issue for water planners in developing countries. We propose a technique derived from Heckman (1976) to accurately measure the expected increase in water use due to access to tap water while controlling for differences in characteristics between connected and non-connected households. Illustration is made on a cross section of 246 households from Dakar, Senegal. We show that getting a tap connection induces an expected increase in water use of 26 L per capita per day.